2011
DOI: 10.1111/j.1526-4610.2011.01882.x
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Behavior and Expression of CGRP‐Related Genes in a Rodent Model of Chronic Migraine

Abstract: a. Objective The objectives of this study were to develop a preclinical rodent model that produces migraine-like behaviors based on International Headache Society diagnostic criteria, to determine whether sex differences are present, and to determine whether expression of CGRP and the genes encoding its receptor in trigeminal ganglion or medulla correlates with those behaviors. b. Background Few animal studies of migraine have tested behaviors associated with migraine diagnostic criteria. In this study, chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
85
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(97 citation statements)
references
References 39 publications
9
85
3
Order By: Relevance
“…Elevated plasma CGRP levels in cranial (26) and systematic circulation were found in patients with migraine, regardless of the presence or aura and outside of attacks (26,27). Of note, CGRP levels were also higher in female than in male patients with migraine (28,29). Moreover, CernudaMorollo´n et al (30) reported higher CGRP levels in patients with chronic migraine (15 headache days per month) than in those with episodic migraine (<15 headache days per month), which might explain our finding that a higher frequency of ambulatory visits for headache within the first year, especially 6 visits, was associated with a greater risk of developing urinary calculi.…”
Section: Discussionmentioning
confidence: 90%
“…Elevated plasma CGRP levels in cranial (26) and systematic circulation were found in patients with migraine, regardless of the presence or aura and outside of attacks (26,27). Of note, CGRP levels were also higher in female than in male patients with migraine (28,29). Moreover, CernudaMorollo´n et al (30) reported higher CGRP levels in patients with chronic migraine (15 headache days per month) than in those with episodic migraine (<15 headache days per month), which might explain our finding that a higher frequency of ambulatory visits for headache within the first year, especially 6 visits, was associated with a greater risk of developing urinary calculi.…”
Section: Discussionmentioning
confidence: 90%
“…The cannula was implanted through the skull under isoflurane anesthesia as previously described in detail. (Stucky, et al, 2011). Briefly, the cannula was placed on the right side of the skull over the occipital lobe 5 mm lateral to midline and halfway between bregma and lambda.…”
Section: Methodsmentioning
confidence: 99%
“…It is hoped that such models will yield insights into mechanisms of chronic migraine transformation and reversion. [81][82][83][84] A recent study in humans suggests that plasma concentrations of CGRP measured between migraine attacks might serve as a biomarker for chronic migraine. 39 Future studies should evaluate the utility of measuring concentrations of CGRP and other vasoactive neuropeptides to predict transformation, predict treatment responses, and assess early responses to migraine prophylaxis.…”
Section: Looking Ahead Researchmentioning
confidence: 99%